How perceived value, environmental awareness, and social identity shape public support for industrial heritage: the mediating role of place attachment - Fu, Yinghang; Dong, Weidan (Frontiers in Psychology, 2025)
IntroductionPublic engagement is critical to the conservation of industrial heritage sites, yet the psychological mechanisms underlying support behaviors remain understudied. This study investigates how perceived value, environmental sustainability awareness, social identity, and perceived government support shape the public’s willingness to participate in and financially support industrial heritage conservation. Particular attention is given to the mediating role of place attachment.MethodsA structured survey was administered to 385 visitors at the “Changtuo 1958” industrial heritage site in Changchun, China. Key constructs—including perceived value, environmental sustainability awareness, social identity, perceived government support, place attachment, willingness to participate, and willingness to pay—were measured using validated multi-item Likert scales. Data were analyzed using structural equation modeling (SEM) to test direct and indirect effects, and mediation analysis was conducted to assess the role of place attachment.ResultsAll four predictors—perceived value, environmental sustainability awareness, social identity, and perceived government support—significantly enhanced both participation and payment intentions. Place attachment partially mediated these relationships, with social identity exerting the strongest overall impact on both outcomes. SEM results confirmed that emotional bonds to the site act as a crucial pathway linking cognitive and social perceptions to public engagement.DiscussionThese findings underscore the importance of affective and identity-based mechanisms in promoting pro-environmental behaviors toward industrial heritage conservation. Strategies to strengthen public support should include fostering emotional connections, enhancing sustainability messaging, and increasing trust in institutional support. The study provides actionable insights for policymakers and heritage managers aiming to enhance sustainable engagement in industrial heritage contexts.